Optimization Design of Concentric Magnetic Gear based on Genetic Algorithm Toolbox of Matlab - Jing Libing; Gao Qixing; Liu Lin; Li Hao; Su Jianhua (Jixie chuandong)
The concentric magnetic gear is a transmission gear with a novel structure and a promising prospect,by using the magnetic field modulation principle,the large torque transmission is realized. On the basis of concentric magnetic gear structure,the modulation magnet ring is improved,the silicon steel is added on the inside of the modulation magnet ring to constitute a mechanical bridge. The model of the improved magnetic gear is simulated by using two dimensional（2D） finite element（FE） method,and the magnetic field and electromagnetic torque are calculated. At the same time,the magnetic field and torque are compared with the common gear. The results show that improved magnetic gear magnetic field is higher than normal- type magnetic gear,lower harmonic content,and torque is also improved. It is significant for the research and application of the concentric magnetic gear.